Pengaruh Media Sosial Terhadap Pemerolehan Bahasa Anak Usia SD - Devi Zakiah Nur Khasanah; Rima Eka Puspitasari; Adelia Febi Kumala Dewi; Kurnia Nur Aisyah; Muhardila Fauziah (Publikasi Inspirasi Indonesia, 2024)
The aim of this research is to help children develop the language and communication skills necessary to survive in today's digital era. In the context of children's language acquisition social media has the potential to promote language continuity and support effective learning. This type of research uses a descriptive analytical approach to provide an in-depth and analytical picture of developments, views and findings in the related field of knowledge. The technique used in data collection is library research. This technique was chosen to explore a deeper and more comprehensive understanding of the research topic, by utilizing scientific literature, journals and other library sources to synthesize and analyze existing information. Social media is an application that requires an internet network as a tool designed to facilitate social interaction and is interactive because it can be used to represent oneself, interact, collaborate, share, communicate with other users and form virtual social bonds. In this day and age, technology has become a part of every individual, in fact many of us depend heavily on technology and the internet, where there are many sites including social media. Therefore, it is very important for parents to supervise when their children start using social media, especially young children, because social media has not only positive impacts but also negative impacts. For this reason, we must have a solution so that all the negative things that happen can be overcome. The solution that we can do is to supervise children when playing on social media so that they can reduce children's habits of saying words that interfere with communication, carry out socialization with parents, set time limits for children playing with gadgets, provide educational games for children, and invite children to play together.